2016
DOI: 10.1371/journal.pone.0159976
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Costs of Treating Hepatitis C Patients in the Era of First Generation Protease Inhibitors – Results from the PAN Study

Abstract: 1. ObjectiveChronic hepatitis C virus infections (HCV) cause a significant public health burden. Introduction of telaprevir (TVR) and boceprevir (BOC) has increased sustained virologic response rates (SVR) in genotype 1 patients but were accompanied by higher treatment costs and more side effects. Aim of the study was to assess outcomes and costs of treating HCV with TVR or BOC in routine care.2. Material and MethodsData was obtained from a non-interventional study. This analysis relates on a subset of 1,786 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…In our cohort, 77.3% of patients had a METAVIR score F4 defined by fibroscan or liver biopsy. 37 Therefore, the more advanced the liver fibrosis, the higher the risk of anemia, as already shown by other studies. 38 However, given the current trend in reducing the use of RBV, 39 the impact of this element will be further reduced.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In our cohort, 77.3% of patients had a METAVIR score F4 defined by fibroscan or liver biopsy. 37 Therefore, the more advanced the liver fibrosis, the higher the risk of anemia, as already shown by other studies. 38 However, given the current trend in reducing the use of RBV, 39 the impact of this element will be further reduced.…”
Section: Discussionmentioning
confidence: 58%
“…The PAN study, a large German study based on first-generation DAAs, reported the same side effect only in 2.4%,37 but in that study, only 17.3% of the cohort presented an advanced fibrosis or liver cirrhosis (determined by AST to platelet ratio index). In our cohort, 77.3% of patients had a METAVIR score F4 defined by fibroscan or liver biopsy 37. Therefore, the more advanced the liver fibrosis, the higher the risk of anemia, as already shown by other studies 38.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Current German guidelines recommend interferon-free regimens as first-choice treatment [ 37 ]. Further, evidence is accumulating that DAA therapies provide a cost-effective means to reduce the morbidity and mortality associated with chronic infection with HCV [ 20 ]. In our study, all patients achieved SVR of 100% 6 months after therapy.…”
Section: Discussionmentioning
confidence: 99%
“…HCV infection leads to liver fibrosis (LF) up to LC and/or hepatocellular carcinoma (HCC) and reduced life expectancy [ 9 , 14 - 18 ]. Successful treatment of HCV infection stops LF progression and partially reverses it [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%